Effect of Isolated Fracture on the Carbonate Acidizing Process - Jia, Cunqi; Huang, Tao; Yao, Jun; Xing, Hongchuan; Zhang, Haiyang (Frontiers in Earth Science, 2021)
Carbonate reservoirs are one of the most important fossil fuel sources, and the acidizing stimulation is a practical technique for improving the recovery of carbonate reservoirs. In this study, the improved two-scale continuum model, including the representative elementary volume (REV) scale model and the upscaling model, is used to study the acidizing process with an isolated fracture. Based on this model, a comprehensive discussion is presented to study the effect of the physical parameters of the isolated fracture on the acidizing results and dissolution images, including the isolated fracture geometry, location, and morphology. Results show that the isolated fracture system is still the target system for the acidizing stimulation. The isolated fracture provides a limited contribution to the core porosity. The permeability of the core sample with fracture can be obviously increased only when the fracture penetrates through the whole sample. The existence of the isolated fracture reduces the consumption of acid solution to achieve a breakthrough. The acidizing curve is sensitive to the change of the length, aperture, and position of the isolated fracture. The acidizing curve difference corresponding to different rotation angles has not changed significantly for clockwise rotation and anticlockwise rotation groups.